An Overview of Interfacial Radiation Chemistry in Nuclear Technology. Issue 3 (11th March 2014) - Jonsson, Mats
Abstract Interfacial radiation chemistry is of key importance in nuclear technology because most materials in the vicinity of radioactive materials in nuclear power plants, reprocessing plants, and repositories for nuclear waste are exposed to ionizing radiation. Corrosion is a crucial issue for the long‐term performance and safety of these installations. Nevertheless, this field is still fairly undeveloped. In this paper, the current state of the art with particular focus on reactions between aqueous radiolysis products and metal or metal oxide surfaces is discussed. The general reactivity of hydrogen peroxide and the hydroxyl radical towards oxide surfaces is discussed on the basis of recent experimental results and DFT calculations. More specific discussions on radiation‐induced surface processes in a future geological repository for spent nuclear fuel are given as relevant examples. This includes radiation‐induced dissolution of spent nuclear fuel in contact with groundwater, radiation‐induced corrosion of copper, and radiation‐induced alterations of bentonite clay. Current knowledge gaps in these areas are highlighted.